Deteksi Dini Tumbuh Kembang Anak di Puskesmas Bontonompo Kab. Gowa - Nur Ilah Padhila; Sunarti Sunarti; Ernasari Ernasari (PT.Mantaya Idea Batara, 2021)
Along with their growth and development, children will experience many things that can have positive or even negative effects, so that efforts to monitor early childhood growth and development can be carried out at all levels of service. Therefore, as a form of implementing the tridarma in higher education, community service is carried out regarding Early Detection of Child Growth and Development which is expected to be able to support the improvement of growth and development in children. This activity aims to increase public knowledge, especially mothers, in early detection of child growth and development. This service activity is carried out through socialization and education on the assessment of child growth and development directly to health cadres and the general public. The results of this community service show that the community is able to understand the assessment of the stage of growth and development in children. Based on this activity, as a form of follow-up, it is hoped that the support and participation of health cadres and puskesmas health workers in assisting the community in assessing and monitoring child development on an ongoing basis.